ChemInform Abstract: Ammonium—Cobalt—Nickel Phosphates, NH4 [Co1‐xNixPO4]·H2O. Issue 44 (14th October 2013) - Torre‐Fernandez, Laura; Trobajo, Camino; de Pedro, Imanol; Alfonso, Belen F.; Fabelo, Oscar; Blanco, Jesus A.; Garcia, Jose R.; Garcia‐Granda, Santiago
Abstract Title compounds with x = 0.00, 0.34, 0.59, 0.70, and 1.00 are prepared by hydrothermal reaction of MCl2 (M: Ni, Co) and solid (NH2)2CO in aqueous H3PO4 (autoclave, 180 °C, 7 d).